FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA DI SEKTOR INFORMAL MASA PANDEMI COVID-19 - Nugraheni, Rashieka Handa; Nugroho Suryo Bintoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The increase in the number of informal workers in Malang City occurred during the 2020 Covid-19 Pandemic. On the other hand, the average wage or salary for informal workers in Malang City experienced a decline when the 2020 Covid-19 Pandemic began. However, the average wage or salary is starting to improve with an increase of 41.05% from 2021 to 2022. The amount of this increase can be indicated to be accompanied by an increase in labor productivity where wages and labor productivity have a very reciprocal relationship. Moreover, productivity is an important element in measuring economic activity. Therefore, the aim of this research is to identify factors that influence labor productivity in the informal sector during the Covid-19 pandemic in Malang City. The data in the research were obtained from Sakernas data for 2021 and 2022. This research used quantitative descriptive methods with cross section data regression. The analysis model used is multiple linear regression analysis. The results of the analysis show that in 2021 training, digital technology, marital status and number of family members will influence the productivity of informal workers. Meanwhile, in 2022 education, training, digital technology, marital status, age and number of family members will influence the productivity of informal workers in Malang City.